PERAN PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS TENAGA KERJA DI KABUPATEN KARANGANYAR - Nugroho, Alifian; Wahyuni, Sri (Res Publica: Jurnal Hukum Kebijakan Publik, 2025)
This research describes and examines problem, first, what is the role of local government in improving the quality of labor in Karanganyar Regency. Second, what are the obstacles faced by The Local Government in improving the quality of labor in Karanganyar Regency. This research is an descriptive empirical legal research. This research approach are statute approach, case approach, and conseptual approach. The research location is at the Department of Trade, Employment, Cooperatives, and Small and Medium Entreprises, Karanganyar Regency. The types and sources of data for this research are primary and secondary data. Data collection tecniques through interviews, observation, and literature study. The data analysis uses qualitative analysis. The results of the research show that the COVID-19 pandemic in Indonesia has resulted difficulty of companies on continuing production activities which has resulted in a decrease of company’s revenue which has resulted in the Termination of Employment for several employees. In overcoming the booming number of unemployed in Karanganyar Regency, The Local Government using The Skill Development Center (SDC) program to improve the quality of the labor. Obstacles faced by Local Government are tha pandemic itself, budget, mismatch between training and work needs, and disinterest in existing job vacancies.